SISTEM INFORMASI TATA KELOLA PERPUSTAKAAN BERBASIS WEB PADA DINAS KEARSIPAN DAN PERPUSTAKAAN PROVINSI GORONTALO - salim, Muh; Ahmad, Sulistiawati R.N; Saleh, Danial (JSAI (Journal Scientific and Applied Informatics), 2021)
The research aims to facilitate the process of processing library data in the form of database storage, resulting in accurate reports, in pandemic times where all employees are required to do their duties from home so that staff in the field of services and technology, staffing, and governance have difficulty processing library data. Although it has used a computer as a means of support, the processing of data libraries is still stored using Ms.office, resulting in ineffectiveness in the work. The application of the information system has helped employees in accelerating the creation and submission of reports carried out in the Ministry of Archives and Library of Gorontalo Province using descriptive methods. The number of visitors who come on average is 51 people/day, and for the month as many as1,224 people. So the total number of visitors in 2020 is 14,688 people.Web-Based Library Governance Information System at the Ministry of Archives and Library of Gorontalo Province can provide convenience in processing Data Library and assist employees in doing their work from home (WFH)